A systematic review of technology use in middle and high school mathematics education: insights from contextual, methodological, and evaluation characteristics - Darmanova, Zhadrassyn; Abylkassymova, Alma; Nurmukhamedova, Zhanara (Frontiers in Education, 2025)
In this systematic literature review, we analyzed empirical studies on the use of technology in mathematics education at the secondary and high school levels in period of 2019-2024. Utilizing the PRISMA flow diagram, we identified 300 studies from three major academic databases: Web of Science, Scopus, and Google Scholar. After applying our inclusion and exclusion criteria, we ultimately selected 25 relevant empirical studies. The entire paper is divided into two parts: the first part focuses on the bibliometric and contextual characteristics of the selected studies, while the second part examines the methodological and evaluative approaches used by researchers to assess the impact of technology on students’ attitudes, beliefs, and academic performance in mathematics. Our findings show that a significant portion of the work in this area involves the use of interactive platforms such as GeoGebra and Kahoot. Moreover, the role of augmented reality in mathematics education has also been investigated to a considerable extent. High school-level content is studied more frequently than middle school content. Regarding methodological approaches, we found a noticeable lack of qualitative and longitudinal studies. Furthermore, there is a need to develop and validate measurement tools across diverse educational settings to ensure comparability and rigor. Finally, certain learning outcomes—such as retention, attitudes, and teamwork—are rarely assessed.